Radiographic Evaluation Of The Success Of Root Canal Treatment In Mandibular Premolars: A Retrospective Cross-Sectional Study - Damla Erkal; Yunus Emre Çakmak; Maira Kopbayeva; Kürşat Er (Clinical Dentistry and Research, 2026)
Background and Aim: Radiographic assessment is essential forevaluating the technical quality of root canal fillings and periapicalstatus after root canal treatment (RCT). This retrospective crosssectionalstudy assessed the radiographic quality of RCT in mandibularpremolars using panoramic radiographs and investigated theassociation between root canal filling quality and periapical lesions.Materials and Methods: Archived digital panoramic radiographswere screened, and 205 radiographs (261 mandibular premolars:34, 35, 44, 45) were included. Two experienced endodontistsindependently assessed filling length (adequate: 0-2 mm fromradiographic apex; short: >2 mm short; overextended: beyond apex),homogeneity, periapical status (lesion absent/present), and iatrogenicerrors. A favorable radiographic outcome required adequate length,homogeneous obturation, no periapical radiolucency, and no iatrogenicerrors. Interobserver agreement was calculated using Cohen’s kappa.Multivariable logistic regression with cluster-robust standard errorsidentified predictors of periapical lesion presence.Results: Overall, 59% of teeth met the predefined radiographic criteria.Periapical lesions were present in 26.1% of teeth. In adjusted analyses,short fillings were strongly associated with lesion presence (P <0.001), and iatrogenic errors were also significant (p = 0.015). Tooth35 showed higher odds than tooth 34 (p = 0.003). Inhomogeneousfillings showed a non-significant trend (aOR = 2.27; p = 0.072), whileoverextension was not associated (p = 0.327). Sensitivity analysiswas consistent and additionally supported filling homogeneity assignificant (p = 0.036).Conclusion: In mandibular premolars evaluated on panoramicradiographs, 59% of teeth met the predefined radiographic criteria.Short filling and iatrogenic errors were independent predictors ofpost-treatment periapical lesions, highlighting the importance ofaccurate working length control and meticulous technique.